2014
DOI: 10.1111/1755-5922.12098
|View full text |Cite
|
Sign up to set email alerts
|

Rosuvastatin May Reduce the Incidence of Cardiovascular Events in Patients with Acute Coronary Syndromes Receiving Percutaneous Coronary Intervention by Suppressing miR‐155/SHIP‐1 Signaling Pathway

Abstract: SUMMARYPurpose: The beneficial effect of rosuvastatin against percutaneous coronary intervention (PCI) related procedural myocardial injury has been determined mostly in patients with acute coronary syndromes (ACS). However, the detailed therapeutic mechanism has not been well studied. Treg percentage values (P < 0.05). In addition, patients with rosuvastatin pretreatment also reduced incidence of 30 days major adverse cardiac events (MACE) compared to the patients with placebo treatment (16 patients vs. 28 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 41 publications
1
47
1
Order By: Relevance
“…Therefore, we suggest that TNF‐α levels might not only serve as a biomarker of the above‐mentioned pathological conditions, but also be implicated in the progress of cardiovascular‐related pathologies. This is in agreement with several studies that have shown a potential benefit of TNF‐α reduction after statin treatment , suggesting that reduced TNF‐α levels might be associated with both treatment efficacy and a reduction in inflammation in these patients. Plasma TNF‐α levels are considered to add prognostic information to that conveyed by CRP or hs‐CRP (another classical acute‐phase protein and an extremely sensitive marker of systemic inflammation) in the prevention of future cardiovascular events .…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, we suggest that TNF‐α levels might not only serve as a biomarker of the above‐mentioned pathological conditions, but also be implicated in the progress of cardiovascular‐related pathologies. This is in agreement with several studies that have shown a potential benefit of TNF‐α reduction after statin treatment , suggesting that reduced TNF‐α levels might be associated with both treatment efficacy and a reduction in inflammation in these patients. Plasma TNF‐α levels are considered to add prognostic information to that conveyed by CRP or hs‐CRP (another classical acute‐phase protein and an extremely sensitive marker of systemic inflammation) in the prevention of future cardiovascular events .…”
Section: Discussionsupporting
confidence: 92%
“…While the functional role of miR-155 in the setting of myocardial infarction has so far remained unclear, several observatory clinical studies have already pointed toward a harmful and potentially important role of miR-155 in human patients with acute coronary syndrome: Matsumoto and coworkers recently found that serum levels of miR-155 were significantly elevated in patients who died after admittance for myocardial infarction compared to patients who survived up to one year [29]. Xie et al published observational data that suggest a partial mediation of the protective effects of statin treatment in acute coronary syndromes via the suppression of miR-155/SHIP-1 signaling pathway [54]. As miR-155 is a multifunctional miRNA with a broad expression pattern across cell types [9], these studies do not allow a conclusive interpretation of miR-155 function in the ischemically challenged heart.…”
Section: Regulation Of Inflammation By Mir-155mentioning
confidence: 99%
“…The clinical study of rosuvastatin treatment in 159 patients with ACS after PCI demonstrated that rosuvastatin reduced the incidence of cardiovascular events through suppressing miRNA-155- SHIP-1 molecular signaling pathway [21]. Moreover, the first clinical trial targeting miRNA-122 using Miravirsen, an antisense oligonucleotide against hepatitis C virus [49], sheds light on clinical application of miRNA inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased serum levels of miRNA-155, along with increased target gene SH2-containing inositol 5′-phosphatase 1 (SHIP-1) expression was associated with reduced incidence of periprocedural MI, lower level of cardiac troponin I, and less inflammatory cytokine (INF- γ , TNF- α , and IL-6) expression after rosuvastatin treatment in post-percutaneous coronary intervention (PCI) patients with acute coronary syndromes (ACS). Therefore, the beneficial effect of rosuvastatin might be explained in part by suppression of the miRNA-155/SHIP-1 signaling pathway [21]. Tian et al observed that the increase of miRNA-155 in CD14 + monocytes from patients with CAD was associated with the elevation of proatherosclerotic factors TNF- α and IL-6, which might affect monocytes [22].…”
Section: Mirna-155 In Cadmentioning
confidence: 99%